IMPLEMENTASI ELECTRONIC GOVERNMENT UNTUK PENYELENGGARAAN PELAYANAN ADMINISTRASI KEPENDUDUKAN - Junaidi . (Universitas Tribhuwana Tunggadewi, 2015)
Population is an important component in a country. Demographic indicators such as the number, growth, composition and distribution of the population affect the economic, social, political, and cultural environment. Population Administration is a series of structuring and regulating activities in the publishing of documents and demographic data through population registration, civil registration, information management and utilization of the results of population administration for public services and the development of other sectors. The purpose of this study is to describe the implementation of e-government in the service of administration, the benefits of e-government implementation and factors that support and hinder the implementation of e-government in the service of the population administration. The results of this study indicate that the implementation of e-government in the service of the population administration has been implemented by the Department of Population and Civil Registration Serdang Bedagai since 2007 that the use of ICT as SIAK and e-ID card in service. The benefit is increased efficiency, effectiveness, transparency, accountability, participation, security and accuracy of demographic data. Factors supporting the leadership commitment, budgets, policies, while human resources, infrastructure and public awareness are obstacles to the implementation of e-government.